2021
DOI: 10.4103/abr.abr_173_20
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis B Virus Markers among Students of Shiraz University of Medical Sciences

Abstract: Background: Protection against hepatitis B virus (HBV) is based on the presence of antibodies against hepatitis B surface antigen (HBsAg). Vaccination of newborns is the most effective means of prevention. This study aimed to evaluate the frequency of anti-HBs antibody (anti-HBsAb), anti-HB core Ab (anti-HBcAb), HBsAg, and HBV DNA among university students in Fars province, Southern Iran. Materials and Methods: In this cross-sectional study, 272 students of Shiraz Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…7 In majority circumstances antibody titers fail to increase due to either improper vaccination or loss of immune response. 8 In long-term follow-up studies of individuals who received 3 doses of the hepatitis B vaccine starting at birth, a significant portion of participants showed declining protection 5-15 years after the initial immunisation 9,10,11,12 and one of the study in India showed 11% to 24% of dental students had a moderate to poor immune response. 13 Similar studies in Pakistan found low anti-HBs titer levels of 25.8% among dental professionals and dental students in Karachi 14 and only 13.7% 15 of healthcare providers in Peshawar who had had vaccinations.Similar study among Multan dental students reported 46.7% of students who had never received vaccinations.…”
Section: Introductionmentioning
confidence: 99%
“…7 In majority circumstances antibody titers fail to increase due to either improper vaccination or loss of immune response. 8 In long-term follow-up studies of individuals who received 3 doses of the hepatitis B vaccine starting at birth, a significant portion of participants showed declining protection 5-15 years after the initial immunisation 9,10,11,12 and one of the study in India showed 11% to 24% of dental students had a moderate to poor immune response. 13 Similar studies in Pakistan found low anti-HBs titer levels of 25.8% among dental professionals and dental students in Karachi 14 and only 13.7% 15 of healthcare providers in Peshawar who had had vaccinations.Similar study among Multan dental students reported 46.7% of students who had never received vaccinations.…”
Section: Introductionmentioning
confidence: 99%